Bioecología y manejo de la cochinilla harinosa de la vid - Becerra, Violeta Cristina; Herrera, Maria Eugenia; Dagatti, Carla Vanina; Mendoza, Graciela Beatriz; Gonzalez, Marcela Fabiana; Navarro, Rosanna Graciela; Turaglio, María Eugenia (Centro Regional Catamarca-La Rioja, 2024)
Ciclo de Jornadas técnicas regionales, 2017